Navigating Nigeria’s Media Landscape Through Information Law: The Journalists’ Perspectives - CHUKWU, Obinna Johnkennedy (Journal of Political And Legal Sovereignty, 2024)
Purpose:This study navigates Nigeria’s media landscape through information law from the journalists’ perspectives. The researcher embarked on this study basically to examine the perceptions and experiences of journalists regarding the role of information law in shaping media practices in Nigeria and to explore the challenges faced by journalists in navigating Nigeria’s media landscape due to information laws. Based on the objectives of this study, two research questions were formulated to serve as a guide for this study.Methodology:This study is anchored on the libertarian theory, and data were collected through interviews. Findings from the study show that information law has a significant impact on the legislation and regulations on press freedom. The legal framework, including the Freedom of Information Act (FOIA) and laws governing defamation, libel, and slander, often shapes journalists' ability to access and disseminate information.Findings:Journalists operate within a legal environment that can either facilitate or hinder their work, with restrictive laws and regulations acting as potential barriers to free and independent journalism. The study concludes that there is an urgent need for legal reforms aimed at strengthening press freedom, safeguarding journalists’ rights, and enhancing public access to information.Implication:Such reforms are essential for fostering a vibrant media environment that serves as a watchdog, holding government and other institutions accountable to the people. Based on the findings of this study, it is recommended that policymakers and legislators should prioritize legal reforms aimed at enhancing press freedom, protecting journalists’ rights, and promoting transparency in Nigeria.